Use of N-acetylcysteine as treatment adjuvant regulates immune response in visceral leishmaniasis: Pilot clinical trial and in vitro experiments - Magalhães, Lucas Sousa; Melo, Enaldo Vieira; Damascena, Nayra Prata; Albuquerque, Adriana Cardoso Batista; Santos, Camilla Natália Oliveira; Rebouças, Mônica Cardozo; Bezerra, Mariana de Oliveira; Louzada da Silva, Ricardo; de Oliveira, Fabricia Alvisi; Santos, Priscila Lima; da Silva, João Santana; Lipscomb, Michael Wheeler; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
This investigation aimed to assess the effect of N-acetylcysteine (NAC) as an adjuvant treatment to alleviate visceral leishmaniasis (VL). The present work includes both blinded randomized clinical intervention and experimental in vitro studies. The clinical trial included 60 patients with VL randomly allocated into two groups: a test group (n = 30) treated with meglumine antimoniate plus NAC (SbV + NAC) and a control group (n = 30) treated with meglumine antimoniate only (SbV). The primary outcome was clinical cure (absence of fever, spleen and liver sizes reduction, and hematological improvement) in 180 days. The cure rate did not differ between the groups; both groups had similar results in all readout indices. The immunological parameters of the patients treated with SbV + NAC showed higher sCD40L in sera during treatment, and the levels of sCD40L were negatively correlated with Interleukin-10 (IL-10) serum levels. In addition, data estimation showed a negative correlation between the sCD40L levels and the spleen size in patients with VL. For the in vitro experiments, peripheral blood mononuclear cells (PBMCs) or PBMC-derived macrophages from healthy donors were exposed to soluble Leishmania antigen (SLA) or infected with stationary promastigotes of Leishmania infantum in the presence or absence of NAC. Results revealed that NAC treatment of SLA-stimulated PBMCs reduces the frequency of monocytes producing IL-10 and lowers the frequency of CD4+ and CD8+ T cells expressing (pro-)inflammatory cytokines. Together, these results suggest that NAC treatment may modulate the immune response in patients with VL, thus warranting additional investigations to support its case use as an adjuvant to antimony therapy for VL.